EFEKTIVITAS MODEL PEMBELAJARAN SQ3R BERBASIS PADLET : MENINGKATKAN KREATIVITAS BELAJAR PAI DAN BUDI PEKERTI DI SMP - Restia Mulina; Chairul Anwar; Listiyani Siti Romlah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study was motivated by the low level of learning creativity among students in the subjects of Islamic Religious Education (IRE) and Character Education, particularly in terms of flexibility and originality of thinking. This situation is evident in low student participation, a lack of self-confidence in,expressing ideas, and a teaching approach that remains largely conventional. Therefore,a learning model is needed that can actively enhance student engagement and creativity. This study aims to determine the effectiveness of the Survey, Question, Read, Recite, Review (SQ3R) learning model based on Padlet in enhancing students’ learning creativity. The method used is a quantitative approach with a quasi-experimental design employing a Posttest-Only Control Group Design. The research sample consisted of two classes: an experimental class using the SQ3R model and a control class using conventional methods. Data collection utilized a learning creativity questionnaire that had been validated for validity and reliability, and the results were analyzed using a t-test. The results of the study indicate that there is a significant difference between the experimental group and the control group, with a p-value of 0.029 < 0.05. This suggests that the implementation of the SQ3R model is effective in enhancing students’ learning creativity, particularly in terms of flexible thinking. This model encourages students to actively ask questions, read purposefully, and creatively restate their understanding. In conclusion, the Padlet-based SQ3R learning model has proven effective in enhancing students’ learning creativity in Islamic Education and Character Education. This model can serve as an innovative alternative learning strategy to create a more active, interactive, and meaningful learning environment.